Development of Augmented Reality-Based History Card Media to Strengthen Chronological Thinking Skills - Brilliantoro Yusuf Ervanda; Rhoma Dwi Aria Yuliantri; Awanis Akalili (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
Chronological thinking skills are an important foundation in historical thinking skills because they help students understand the relationships between historical events in a coherent, logical, and meaningful manner. However, the results of a needs analysis at SMAN 2 Klaten indicate that students still experience difficulties understanding the sequence of events in the material "Efforts to Maintain Indonesian Independence." In addition, the learning media used are still dominated by textual materials, while students want more interactive, visual media that align with the development of digital technology. The purpose of this study is to develop Augmented Reality-based History Card learning media to strengthen students' chronological thinking skills in the material Efforts to Maintain Indonesian Independence. The study used the Research and Development (R&D) method, with the Borg and Gall model comprising 10 development stages. The resulting product is a history card integrated with an Android-based Augmented Reality application that includes AR-scanning features, visualisation of historical events, location maps, learning materials, and evaluation quizzes. Based on the validation results, the material experts assigned a feasibility score of 88% to the developed media, 92.8% to media experts, and 90% to history teachers. All assessment results were classified as very feasible. The media's feasibility rate was 82.3% in a small-group trial with six students and 81% in a large-group trial with 30 students. The media's effectiveness was tested through pretests and posttests, which demonstrated an increase in student performance after using the developed learning media. These findings indicate that the developed media meets the criteria of validity, practicality, and effectiveness, making it suitable for use in strengthening students' chronological thinking skills in history learning.